THE CONTENT OF FORMING LIFE SKILLS IN LANGUAGE EDUCATION - Klaraxon Mavlonova (Journals Park Publishing, 2024)
Focusing exclusively on the upbringing of students in secondary education, preparing them for life by developing 21st-century skills, preventing infringements occurring in schools, independently solving their problems in various situations, teaching them how to deal with violence and fighting, motivational solutions to leadership, media skills, integrating global civil skills into young people is one of the issues. This article discusses the content of developing life skills in the language (Uzbek) education.
Keywords: 21st century skills, language education, violence and fighting, global citizenship, leadership, mediation.